1966
DOI: 10.1063/1.1761810
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Electron Diffusion and Ion Acceleration in a Low-Density Plasma

Abstract: Ion and electron transport properties have been measured in a steady state, weakly turbulent plasma that was subjected to crossed E and B fields. The geometry permits quantitative measurements of electron and ion currents. The ion gyro radius is large compared to the apparatus dimensions. Measurements of the potential gradients, Hall currents, and ion velocity show that the ions are freely accelerated through the plasma by electrostatic forces. However, an ``anomalous diffusion'' of electrons is observed since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
220
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(231 citation statements)
references
References 9 publications
11
220
0
Order By: Relevance
“…The perhaps most studied are Hall thrusters, which were introduced decades ago and recently gained renewed and increased interest. 36,[49][50][51][52][53][54][55] At least seven different modes and types of instabilities have been identified, all operating in different, sometimes overlapping ranges of frequency. Some are in the 10-100 kHz range and have other similarities; among them are the breathing mode, rotating spoke mode, and azimuthal drift magnetosonic waves.…”
Section: Fig 6 (Color Online)mentioning
confidence: 99%
“…The perhaps most studied are Hall thrusters, which were introduced decades ago and recently gained renewed and increased interest. 36,[49][50][51][52][53][54][55] At least seven different modes and types of instabilities have been identified, all operating in different, sometimes overlapping ranges of frequency. Some are in the 10-100 kHz range and have other similarities; among them are the breathing mode, rotating spoke mode, and azimuthal drift magnetosonic waves.…”
Section: Fig 6 (Color Online)mentioning
confidence: 99%
“…A third possible mechanism for electron transport, the so-called rotating spoke, has also been investigated in an annular geometry with an axial electric field and radial magnetic field, where it was found that the spoke could quantitatively explain the level of anomalous transport 6 . A qualitative understanding for how the spoke could contribute to electron transport across the magnetic field is as follows: a spoke, or region of increased density, would experience charge separation due to only the electrons being magnetized and undergoing the azimuthal E × B drift.…”
mentioning
confidence: 99%
“…It is of particular interest because of its connection to electron transport across the magnetic field 3,6 . Anomalous electron cross-field transport is an important problem in Hall thruster physics and it is one of the major impediments to predictive modeling of the thruster 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed using Langmuir probes in the thruster channel which measure fluctuations in plasma density and temperature corresponding to an m=1 mode near the anode that rotates at about 10% of the local ExB speed 3,4 . Measurements can also be made with a fast camera, which registers a region of increased visible light emission that rotates at the spoke frequency 4,5 .…”
Section: Introductionmentioning
confidence: 99%